Analisis Pengaruh Karakteristik Audit, Karakteristik Perusahaan, dan Proporsi Komisaris Independen terhadap Pertukaran Auditor pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Supriyanto Supriyanto; Heni Rachmawati (Global Financial Accounting Journal, 2021)
Auditor switching occurs when the old Public Accounting Firm (PAF) is replaced with a new PAF. This study is aim to analyze the factors that effect auditor switching to happen. Purposive sampling method was used in this study to to obtain the sample and sourced from the companies’ annual reports listed on the Indonesia Stock Exchange from 2015 to 2019. The test used binary logistic regression and was processed using the SPSS version 21 program. The results of data analysis indicate that financial distress, auditor reputation and opinion auditors have a significant and positive impact on auditor switching. Profitability has a significant and negative impact on auditor switching. Changes in management and the proportion of independent commissioners have no significant impact on auditor switching.